2009
DOI: 10.1136/tc.2008.028241
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use among sexual minorities in the USA, 1987 to May 2007: a systematic review

Abstract: No language restrictions were used. Abstracts were identified in the literature search (n = 734) and were independently read and coded for inclusion or exclusion by two reviewers. When agreement was not reached, a third reviewer acted as arbitrator. Abstracts were included if they presented data collected in the US from 1987 to May 2007 and reported prevalence or correlation of tobacco use with sexual minority status. Studies reporting data from HIV-positive samples were excluded. The identified articles (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
240
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(262 citation statements)
references
References 89 publications
22
240
0
Order By: Relevance
“…First, consistent with prior research, we found that sexual minorities in our sample had significantly higher (nearly two-fold) current smoking status than heterosexuals (Lee et al, 2009). For the year the NCHA sample data were collected, the national current smoking (i.e., smoked ≥100 cigarettes in lifetime and smoked every day or some days), prevalence was 21.8% for people aged 18-24 years, with approximately 28.0% of men and 15.6% of women being current smokers within the age range of 18-24 years (Dube et al, 2010).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…First, consistent with prior research, we found that sexual minorities in our sample had significantly higher (nearly two-fold) current smoking status than heterosexuals (Lee et al, 2009). For the year the NCHA sample data were collected, the national current smoking (i.e., smoked ≥100 cigarettes in lifetime and smoked every day or some days), prevalence was 21.8% for people aged 18-24 years, with approximately 28.0% of men and 15.6% of women being current smokers within the age range of 18-24 years (Dube et al, 2010).…”
Section: Discussionsupporting
confidence: 78%
“…We use the term socially based stressor to indicate that the stressor was interpersonal and originated from the social environment, rather than a biologically based stressor (e.g., genetic or hormonal factors). There is substantial evidence demonstrating higher smoking prevalence among sexual minority men and women when compared with heterosexual men and women (Lee et al, 2009), and our initial hypotheses test whether these differences in smoking prevalence endure with our sample (i.e., compared with their heterosexual peers, significantly more sexual minority individuals will report smoking).…”
Section: Associations Of Discrimination and Violence With Smoking Amomentioning
confidence: 99%
See 1 more Smart Citation
“…2 Almost all adult daily smokers began before age 26. 3 In addition, lesbian, gay, bisexual, and transgender (LGBT) individuals smoke at higher rates than the general population, 4 and this disparity extends to lesbian, gay, and bisexual young adults. 5 In a recent study by Rath and colleagues, 5 35% of lesbian and gay young adults and 27% of bisexual young adults had smoked in the past 30 days, compared to 18% of heterosexual young adults.…”
Section: Introductionmentioning
confidence: 99%
“…For example, African Americans who perceive racial/ethnic discrimination have greater odds of current smoking (Borrell, Artazcoz et al, 2010;Purnell et al, 2012). The prevalence of smoking also tends to be higher among other minority groups at high risk for discrimination (Greene & Britton, 2012;Lee, Griffin, & Melvin, 2009). Smoking is hypothesized to be one mechanism for coping with discrimination and the psychological distress (e.g., depressive symptoms, anger) that often accompanies such experiences (Purnell et al, 2012).…”
mentioning
confidence: 99%